1993
DOI: 10.1007/bf00033765
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of resistance to Karnal bunt (Tilletia indica (Mitra)) in bread wheat

Abstract: An analyis of an Fl-based incomplete diallel was conducted involving 11 parents with different levels of resistance to Karnal bunt (Tilletia indica (Mitra)). It demonstrated that general combining ability (GCA) and thus additive or additive × additive gene effects were very important in the inheritance of resistance, accounting for 86.9% of the variation. Further analysis concentrated on F3 lines derived from individual random F2 plants from crosses with resistant varieties having the highest negative GCA effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The distribution of KB disease severity on the RILs was skewed toward that of the resistant-parent in three experiments, suggesting the segregation of multiple genes with dominant or complementary gene action in wheat line HD29. This is consistent with the results of previous studies (Morgunov et al 1994;Fuentes-Dávila et al 1995). The heritability of 0.69 on entry mean basis for KB resistance in this population is consistent with other findings showing that resistance to KB in wheat is highly heritable and under relatively simple genetic control Nelson et al 1998).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The distribution of KB disease severity on the RILs was skewed toward that of the resistant-parent in three experiments, suggesting the segregation of multiple genes with dominant or complementary gene action in wheat line HD29. This is consistent with the results of previous studies (Morgunov et al 1994;Fuentes-Dávila et al 1995). The heritability of 0.69 on entry mean basis for KB resistance in this population is consistent with other findings showing that resistance to KB in wheat is highly heritable and under relatively simple genetic control Nelson et al 1998).…”
Section: Discussionsupporting
confidence: 82%
“…Previous genetic studies on KB resistance in wheat indicated that one to six major genes condition resistance in various wheat germplasms (Morgunov et al 1994;Fuentes-Dávila et al 1995;Singh et al 1995aSingh et al , b, 1999Villareal et al 1995). Six wheat chromosomes (1D, 2A, 3B, 3D, 5D and 7A) were identified as influencing reaction to the pathogen (Gill et al1993;Singh et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Pooled y^ confirmed these results. Morgunov et al (1994) also reported the monogenic control of resistance in four resistant genotypes.…”
mentioning
confidence: 96%
“…The best way to control this disease is through the use of resistant cultivars. Breeding for Karnal bunt resistance is a major activity at CIMMYT (International Maize and Wheat Improvement Center) and in a few national programmes in India (Morgunov et al 1994). To support these programmes, knowledge of the genetics of resistance is important.…”
mentioning
confidence: 99%
See 1 more Smart Citation